POLITIK HUKUM PEMBERLAKUAN PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA NOMOR 133 TAHUN 2015 TENTANG PENGUJIAN BERKALA KENDARAAN BERMOTOR DI KOTA PEKANBARU TAHUN 2019 - Lestari, Putri; Firdaus, Emilda; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In terms of creating and guaranteeing the technical safety of motorized vehicles, an act of testing motorized vehicles is required. This can be seen with the issuance of Law Number 22 of 2009 concerning Road Traffic and Transportation and Regulation of the Minister of Transportation Number 133 of 2015 concerning Periodic Testing of Motorized Vehicles. One of the tasks of the Pekanbaru City Transportation Service is to carry out motor vehicle testing. The results of the pre-research found various phenomena in the implementation of motor vehicle testing, namely not optimal motor vehicle testing services, less than optimal motor vehicle testing equipment due to old equipment, limited funding sources from the Pekanbaru City Budget to facilitate all obstacles that occur. The purpose of writing this thesis, namely, firstly, to find out the legal politics of implementing the Periodic Testing of Motorized Vehicles in the City of Pekanbaru in 2019, secondly, to find out that the Periodic Motorized Vehicles in the City of Pekanbaru in 2019 are in accordance with the benefits of law in Indonesia.The type of research on the Political Law of the Enforcement of the Regulation of the Minister of Transportation of the Republic of Indonesia Number 133 of 2015 concerning Periodic Testing of Motorized Vehicles in the City of Pekanbaru in 2019 which is a sociological law research, namely research that focuses on individual or community behavior in relation to the law.From the results of the research problem there are two main things that can be concluded. First, that the legal politics of the enactment of a ministerial regulation has been relevant enough for testing but only for the technical and non-technical vehicle checking section. Second, the benefits of the Regulation of the Minister of Transportation of the Republic of Indonesia Number 133 of 2015 concerning Periodic Testing of Motorized Vehicles in Pekanbaru City can be felt by the driver, namely it is safer to drive and fulfills the needs of carrying out obligations as citizens. Meanwhile, the implementation of legal politics in the field is still not optimal. The author's suggestions, First, in order for the implementation of the legal politics of this enforcement to be carried out to the maximum, it is necessary to add additional rules governing smart cards that have been applied in motor vehicle testing. Second, the Pekanbaru City Transportation Service through UPTD PKB to act decisively on vehicle owners who do not test motorized vehicles by being given sanctions that focus more on coaching and fines, with the aim of increasing Regional Original Income (PAD), in order to provide a deterrent effect and cause legal benefits.Keywords: Legal Politics, Vehicles, Motorcycles, Safety